Իրաքում իրադրության շուրջ ընդունված ՄԱԿ–ի բանաձևերն ու որոշումները (2005-2007 թթ.) - Սամվելյան, Կարինե (Ասողիկ հրատ.)
The article deals with the analyses of the Resolutions and Statements of the Security Council about the Situation in Iraq's political transition process, new plinse in this transition, calling upon the international Community, particularly countries in the region and Iraq's neighbors to Support the Iraqi people in their pursuit of peace, stability, security, democracy and prosperity.
Keywords: Պատմություն; Քաղաքականություն; Իրաք